2019
DOI: 10.2174/1573405614666180322141259
|View full text |Cite
|
Sign up to set email alerts
|

Heart Disease Prediction System Using Decision Tree and Naive Bayes Algorithm

Abstract: The huge information of healthcare data is collected from the healthcare industry which is not “mined” unfortunately to make effective decision making for the identification of hidden information. The end user support system is used as the prediction application for the heart disease and this paper proposes windows through the intelligent prediction system the instance guidance for the heart disease is given to the user. Various symptoms of the heart diseases are fed into the application. The user precedes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The representation of data in the form of the tree is easily understood and this method can handle multidimensional data. Recently, the data mining method has been reported in the field of heart disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…The representation of data in the form of the tree is easily understood and this method can handle multidimensional data. Recently, the data mining method has been reported in the field of heart disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…NB is a simple classifier that predicts and assigns class labels to external data based on vectors of descriptors for a finite set of training observations. The NB classifier posits that each descriptor contributes independently to the probability that an observation belongs to a specific class (e.g., disease or no disease) [ 37 40 ]. The chance of an observation belonging to a specific class is calculated by multiplying the individual probabilities of that class within each individual descriptor [ 37 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The NB classifier posits that each descriptor contributes independently to the probability that an observation belongs to a specific class (e.g., disease or no disease) [ 37 40 ]. The chance of an observation belonging to a specific class is calculated by multiplying the individual probabilities of that class within each individual descriptor [ 37 40 ]. We implemented NB learner node within KNIME Analytics Platform with the following parameters: default probability = 0.0001, minimum standard deviation = 0.0001, threshold standard deviation = 0.0 and maximum number of unique nominal values per attribute = 20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of the Naï ve Bayes and Decision Tree algorithms to predict heart diseases was studied in another research [10], the results of their model showed that Naï ve Bayes is more powerful in term of accuracy than Decision Tree.…”
Section: Related Workmentioning
confidence: 99%